Hydronephrosis and pelvic rupture due to calculus with completely normal laboratory results - Burak Demirci; Burak Akın; Selman Gündoğan; Göker İhsan Özbilir; Mehmet Oktay Alkan; Abuzer Coşkun (Emergency Care Journal, 2024)
Both side pain and urinary system pathologies are common reasons for admission to emergency departments. Spontaneous renal pelvic rupture is also very rare. Existing renal anomalies and calculi also increase the risk of rupture. Here, we present a 50-year-old male case who developed unilateral renal pelvis rupture spontaneously without trauma.